Longitudinal Changes in Physical Activity Level, Body Mass Index, and Oxygen Uptake Among Norwegian Adolescents - Lagestad, Pål; van den Tillaar, Roland; Mamen, Asgeir (Frontiers in Public Health, 2018)
Several studies have investigated activity levels among adolescents, but no study has examined longitudinal changes in physical activity level, body mass and oxygen uptake among the same adolescents from the age of 14 to 19 years. The present study examined data from a research project that included a group of randomly selected students (N = 116) with objective measurements of physical activity (accelerometer data), self-reported physical activity level, and body mass and oxygen uptake during a five-year period. The results show a significant decrease in the accelerometer-based physical activity level over time, from age 14 to 19. At 14 years of age, the minutes of moderate and/or vigorous physical activity was 66.7 min/day, but was less than half, at only 24.4 min/day, at 19 years of age. The self-reported activity data show a decrease in girls’ general activity level over time, while boys’ activity level during school breaks decreased strongly during the period: at age 14, 61% of the boys were classified as active, while at age 19, only 11% were physically active. Furthermore, body mass index increased during the period for both genders, while oxygen uptake decreased. Since both BMI and maximal oxygen uptake are important risk factors for future CVD, these findings point towards the importance of maintaining a high activity level during childhood and adolescence, in order to keep fit later in life.